N-Substituted 5-Amino-6-methylpyrazine-2,3-dicarbonitriles: Microwave-Assisted Synthesis and Biological Properties - Ondrej Jandourek; Martin Dolezal; Pavla Paterova; Vladimir Kubicek; Matus Pesko; Jiri Kunes; Aidan Coffey; Jiahui Guo; Katarina Kralova (Molecules, 2014)
In this work a series of 15 N-benzylamine substituted 5-amino-6-methyl-pyrazine-2,3-dicarbonitriles was prepared by the aminodehalogenation reactions using microwave assisted synthesis with experimentally set and proven conditions. This approach for the aminodehalogenation reaction was chosen due to its higher yields and shorter reaction times. The products of this reaction were characterized by IR, NMR and other analytical data. The compounds were evaluated for their antibacterial, antifungal and herbicidal activity. Compounds 3 (R = 3,4-Cl), 9 (R = 2-Cl) and 11 (R = 4-CF3) showed good antimycobacterial activity against Mycobacterium tuberculosis (MIC = 6.25 µg/mL). It was found that the lipophilicity is important for antimycobacterial activity and the best substitution on the benzyl moiety of the compounds is a halogen or trifluoromethyl group according to Craig’s plot. The activities against bacteria or fungi were insignificant. The presented compounds also inhibited photosynthetic electron transport in spinach chloroplasts and the IC50 values of the active compounds varied in the range from 16.4 to 487.0 µmol/L. The most active substances were 2 (R = 3-CF3), 3 (R = 3,4-Cl) and 11 (R = 4-CF3). A linear dependence between lipophilicity and herbicidal activity was observed.